The Reduction Of Water Level In Used Cooking Oil Using Bagasse Charcoal (Saccharum officinarum) - Kharisma Islamia Nanda Giovani; Purwati Purwati (Jurnal Farmasi (Journal of Pharmacy), 2022)
Recycling technology processes used cooking oil into reusable oil using bagasse as an absorbent material,  to determinate the decrease in water content in used cooking oil using bagasse chacoal. the reseach method is experimental. The sample used is used cooking oil. Water level before the addition of bagasse charcoal was 0,3%. This results after the additional of bagasse charchoal with variation of immersion time 1x24 hours, 2x24 hours and 3x24 hours was 0,1%, 0,03%, and 0,02%.There is reducing in water level after soaking using bagasse charcoal. Water level from used cooking oil more smaller after the addition of soaking time by bagasse charcoal.